EIMERIA AUBURNENSIS AND EIMERIA BOVIS OF PROTOZOA GASTROINTESTINAL INFECTED ON FEMALE BALI CATTLE IN NUSA PENIDA - Indraswari, Anak Agung Sagung; Suwiti, Ni Ketut; Apsari, Ida Ayu Pasti (Buletin Veteriner Udayana, 2017)
Gastrointestinal protozoal infections still be factors which affect health bali cattle and causing economic losses for farmers. Bali cattle reared in Nusa Penida designated as pure. Therefore, this study aimed to determine the prevalence and identify the type of gastrointestinal protozoa in Nusa Penida. A sample of faeces were taken from 100 cows bali female, checked using Zajac and Conboy method (2012). The identification is based on morphology and morphometry. While the prevalence is determined by the way, the number of infected samples divided by the number of samples examined and multiplied by one hundred percent. Results showed the prevalence of gastrointestinal protozoa that infects of Bali cattle female at Nusa Penida is twenty percent, with two types of protozoa infection is Eimeria auburnensis and Eimeria bovis
Keywords: sapi bali; Nusa Penida; Eimeria auburnensis; Eimeria bovis